An experimental investigation into quasi-static and fatigue damage development in bolted-hole specimens. (August 2015) - Nixon-Pearson, O.J.; Hallett, S.R.
Abstract: An extensive experimental program has been carried out to investigate and understand the sequence of damage development throughout the life of bolted-hole composite laminates under quasi-static loading and tension–tension fatigue. Quasi-isotropic carbon/epoxy laminates, with stacking sequence [452 /902 /-452 /02 ]S defined as ply scaled and [45/90/-45/0]2S defined as sub-laminate scaled, were used. Specimens were cycled at 5 Hz with various amplitudes to 1 × 10 6 cycles unless failure occurred prior to this limit. For all cases an R ratio of 0.1 was used. Bolt washer pressures of 23 MPa and 70 MPa were investigated. For the ply-level case, the quasi-static test showed both delamination and fibre-dominated pull-out failures for a washer pressure of 23 MPa, and pull-out failure only for 70 MPa. Delamination dominates in fatigue tests. For the sub-laminate case the tests failed by pull-out in both quasi-static and fatigue tests for all washer pressures. It is shown in this paper how the role of delamination is critical in the case of fatigue loading and how this interacts with bolt clamp-up forces. A number of tests were analysed for damage using X-ray CT scanning and comparisons of damage are made with tests from previous open-hole studies.